Penganggaran Sektor Pendidikan Daerah: Analisis Pada Dinas Pendidikan Kota Surabaya Tahun 2025 - Setya Utami, Adinda Nur; Ramandhani, Amalia; Anita Fitrie, Revienda; Fanida, Eva Hany; Revienda Anita Fitrie (Jurnal Administrasi Publik dan Bisnis, 2026)
Low budget absorption in local government work units remains an unresolved issue in many regions in Indonesia, including the education sector. This study aims to analyze the budget planning mechanism, the stages of budget preparation and approval, the influencing factors, and the relationship between planning quality and budget absorption levels in the Surabaya City Education Office. The study used a qualitative approach through literature review. The results indicate that the budgeting process has followed the normative flow according to regulations, but is still hampered by an incremental approach in proposal preparation, weak coordination between agencies, limited human resource competencies, and the lack of integrated performance data. The low budget absorption and the resulting backlog at the end of the year are proven to be rooted in weaknesses in the planning stage, not solely in implementation. This study emphasizes that improving regional budgeting requires a comprehensive and simultaneous approach at all stages of the budget cycle.